Two percolations model for conductivity-salt concentration in PVC-LiPF6 system - R.H.Y. Subban; M.Z.A. Yahya; R. Puteh; A.K. Arof (Indonesian Journal of Physics, 2004)
Lithium hexafluorophosphate (LiPF6) doped polyvinyl chloride (PVC) polymer electrolytes were prepared by the solution cast technique. LiPF6 has been claimed as the best salt for use in electrolytes for lithium ion batteries. In this work, 1.0 g of PVC and 1.0 g of LiPF6 were dissolved in tetrahydrofuran (THF). The LiPF6 was then substituted with LiCF3SO3 in different weight percentages. The solutions were cast in different petri dishes and left to form films at room temperature. The films were kept in a dessicator for a period of one week to ensure complete dryness. Impedance spectroscopy was used to obtain the bulk resistance from which the conductivity was calculated. The conductivity-salt concentration graph showed two peaks at 0.2g LiCF3SO3 and 0.8 g LiCF3SO3. In glasses, the conductivity is due to the conduction of cations, but in polymers both anions and cations are conducting. In some cases, the transference number of anions is greater than that of the cations. In most cases, the conductivity-salt concentration graph shows only one peak. In such observation, increase in conductivity is explained by the increase in number of free mobile ions and the decrease in conductivity is attributable to ion reassociation. The results in this work cannot be satisfactorily explained by the above mechanism. The two salient peaks observed maybe plausibly explained by the two percolations model in which both positive and negative ions contribute to the conductivity. The first peak is attributed to the lithium ions and the second peak is attributed to the PF6- and CF3SO3- ions. This is also in accordance to the results from transient ionic current experiments, which indicate that the cations have a higher mobility than anions.